What do Health Workers say About Rural Practice? - Eunice Okyere; Paul Ward; Kissinger Marfoh; Lillian Mwanri (SAGE Publishing, 2021)
Adequately staffed rural health services improve healthcare delivery and health outcomes, yet this is lacking in rural Ghana. We used a descriptive qualitative design to understand the contextual issues that affect rural practice, in the Upper East Region, Ghana. Sixty-eight in-depth interviews were conducted with healthcare workers and analysed thematically. Four themes were identified: types of postings to rural settings, healthcare workers' perceptions of their rural postings, perceived enablers and motivators for rural practice, and perceived challenges and barriers to rural practice. While adequate supervision and family proximity are needed to improve the feelings of loneliness, isolation and neglect in rural areas, challenges and barriers such as inadequate security, unstable electricity supply, language barrier, lack of equipment and transport/ambulance have been identified to have negative influence on healthcare workers. The findings highlight the need for healthcare managers to improve fairness and transparency in the posting and reshuffling processes of healthcare workers.